PENERAPAN STRATEGI THINK TALK WRITE UNTUK MENINGKATKAN HASIL BELAJAR IPA MATERI KEANEKARAGAMAN MAKHLUK HIDUP PADA SISWA KELAS VIID SMP NEGERI 6 JEMBER TAHUN PELAJARAN 2016/2017 - Sumarjono Sumarjono (Universitas Jember, 2020)
Abstract.Think talk write learning strategy is learning where students are given the opportunity to start learning by understanding the problem first, then being actively involved in group discussions, and finally writing in their own language the learning outcomes they get. The purpose of this research is to improve the learning outcomes of Science Students in Class VIID of SMP Negeri 6 Jember with think talk write learning strategies. This research method uses a qualitative approach, this type of research is a type of classroom action research (CAR). The class action in this study was carried out with 2 cycles. Each cycle carried out improvements to be achieved through the reflection phase. The results showed that the application of the think talk write strategy could improve the learning outcomes of Grade VII D. Cycle 1 students achieved a minimum completeness criteria of 72.5%. whereas in cycle 2 it was 87.5% Keywords: Think talk write strategy, science learning outcomes, diversity of living things